PASCAL PROGRAMMING TO CALCULATE DEPRECIATION ON FIXED ASSETS USING THE STRAIGHT-LINE - Nurrakhmat Nurrakhmat; Sapta Aji S. M., SKom, MMSI (Jurnal Sistem Informasi, 1998)
Accounting system is good and right will be able to lead a successful companybecause of accounting is one of the providers of financial information that will assistin the estimation results of operations. One of these linkages in accounting is tocalculate the depreciation that usually occurs in the assets owned by the company.